Clinical PET and PET/CT Principles and Applications - Kim, E. Edmund; Lee, Myung-Chul.; Inoue, Tomio; Wong, Wai-Hoi.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Clinical PET and PET/CT, 2nd Edition presents a valuable overview of the basic principles and clinical applications of PET and PET/CT. Emphasis is placed on the familiarization of normal distribution, artifacts, and common imaging agents such as FDG in conjunction with CT, MRI, and US to establish the clinical effectiveness of PET and PET/CT. Practical information about updated PET and PET/CT scanners, imaging processing, correlation, and quantification of PET and PET/CT measurements is also presented. This book is divided into two sections, the first half dealing with the basic principles of PET and PET/CT for instrumentation, fusion, radiopharmaceuticals, radiosynthesis, safety, and cost analysis. The second part of this volume presents chapters on the clinical techniques and applications of PET and PET/CT for common oncologic, cardiologic, and neurologic diseases. Numerous full color images provide comprehensive coverage on essential clinical PET and PET/CT studies.
1 -- Principles of Positron Emission Tomography Imaging 2 -- Production of Isotopes 3 -- Principles of PET/CT 4 -- Radiopharmaceuticals 5 -- Automated Synthesis of Radiopharmaceuticals 6 -- Cost Analysis and Effectiveness of PET and PET/CT 7 -- Technical Principles, Radiation Safety, and Image Interpretation 8 -- Normal and Variable Patterns in PET 9 -- Artifacts in FDG-PET and PET/CT 10 -- Radiation Dosimetry in F-18 FDG PET/CT 11 -- Current Status of PET in the World 12 -- Epilepsy 13 -- Neurodegenerative Diseases 14 -- Cerebrovascular Disease and PET 15 -- Brain Tumors 16 -- Head and Neck Tumors 17 -- Lung and Pleural Cancers 18 -- Breast Cancer 19 -- Coronary Artery Disease 20 -- Myocardial Viability 21 -- Atherosclerosis 22 -- Esophageal, Gastric, and Pancreatic Cancers 23 -- Hepatobiliary and Small Bowel Cancers 24 -- Colorectal Cancer 25 -- Urologic Cancer 26 -- Gynecologic Cancer 27 -- Lymphoma 28 -- Melanoma, Myeloma, and Sarcoma 29 -- Carcinoma of Unknown Primary 30 -- 18F-FDG PET in the Evaluation of Infectious and Inflammatory Diseases 31 -- PET in Radiation Treatment 32 -- Evidence-Based PET 33 -- PET/MRI.
Keywords: Medicine; Radiology, Medical; Nuclear medicine; Medicine & Public Health; Imaging / Radiology; Nuclear Medicine; Diagnostic Radiology